1993
DOI: 10.1002/aheh.19930210106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deicing‐Salts on Heavy Metal Mobility Zum Einfluß von Streusalzen auf die Beweglichkeit von Schwermetallen

Abstract: Heavy metal input into roadside soils and effects of deicing salts are often discussed as separate environmental problems. However, a relationship between salt input and heavy metal mobility has already been detected in laboratory tests. During a 2-year field study, the soil solution of a roadside soil was continuously sampled. The results of soil solution analysis not only showed a strong rise in deicing-salt related sodium, calcium and chloride concentrations, but also high zinc and cadmium values in winter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In column study, Norrström [28] demonstrated that a large part of Pb, Cd and Zn in highway roadside soils are vulnerable to leaching when exposed to a high NaCl (5.84 g/L) concentration. From field studies, Bauske and Goetz [29] also found a strong effect of NaCl solution on Cd and Zn. Additionally, studies have been conducted to examine the remobilization of heavy metals adsorbed onto filter materials used for stormwater treatment [6,25].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In column study, Norrström [28] demonstrated that a large part of Pb, Cd and Zn in highway roadside soils are vulnerable to leaching when exposed to a high NaCl (5.84 g/L) concentration. From field studies, Bauske and Goetz [29] also found a strong effect of NaCl solution on Cd and Zn. Additionally, studies have been conducted to examine the remobilization of heavy metals adsorbed onto filter materials used for stormwater treatment [6,25].…”
Section: Introductionmentioning
confidence: 95%
“…Increased mobility of heavy metals coincident with road salt applications have been observed in road side soils and filter media used in stormwater filtration systems by various mechanisms, including the competition of salt derived cations with positively charged heavy metal species for sorption sites on the solid phase (ion exchange), lowered pH, formation of chlorocomplexes and possible colloid dispersion [27][28][29]32]. The mobility of heavy metals induced by NaCl application might not behave in the same way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of high Cl concentrations leads to a strong decrease in the adsorption of Cd ions in soils (Doner, 1978;Boekhold et al, 1993;Lumsdon et al, 1995). The strong influence of salt concentration on the mobilization of metals has already been observed by many other authors dealing with the topic of road runoff and roadside soils (e.g., Bauske & Goetz, 1993;Strong, 1990, Amrhein et al, 1992;Bäckström et al, 2004, Ramakrishna andViraraghavan, 2005). Li et al (2015) determined an extensive mobilization of Cd soil leachate by salts, accounting for about 21% of the total Cd in the soil.…”
Section: Ecmentioning
confidence: 68%
“…Li et al (2015) determined an extensive mobilization of Cd soil leachate by salts, accounting for about 21% of the total Cd in the soil. Bauske & Goetz (1993) examined concentrations of Cd and Zn that had increased by a factor of 20 in highway soil solutions during the utilization of de-icing salts in winter. Salimi et al (2015) found that the Cl-ion formed complex ions with Cd to CdCl+, CdCl3-, and CaCl4-.…”
Section: Ecmentioning
confidence: 99%